Adobe Photoshop CS5 : restoration and retouching for digital photographers only - Fitzgerald, Mark (Mark Allen) (For Only., 2010)
Showcases the tools and techniques required to digitally restore antique images, retouch portraits, and repair faded and damaged photographs using Adobe Photoshop CS3--